Tai Chi for fall prevention and balance improvement in older adults: a systematic review and meta-analysis of randomized controlled trials - Chen, Weidong; Li, Min; Li, Hai; Lin, Yanzhao; Feng, Zhoushan (Frontiers in Public Health, 2023)
Background and Objective: As the population ages, the health of older adults is becoming a public health concern. Falls are a significant threat to their health due to weakened balance.This study aims to investigate the beneficial effects of Tai Chi on fall prevention and balance improvement in older adults.We conducted a systematic review and meta-analysis of randomized controlled trials related to Tai Chi, falls, and balance ability, searching PubMed, Embase, and Cochrane Library databases from their establishment until December 31, 2022. Two independent reviewers performed the search, screening of results, extraction of relevant data, and assessment of study quality. This study followed the PRISMA guidelines for systematic review and meta-analysis.Totally 24 RCTs were included for meta-analysis, and the results showed that Tai Chi can effectively reduce the risk of falls in older adults (RR: 0.76, 95% CI: 0.71 to 0.82) and decrease the number of falls (MD [95% CI]: -0.26 [-0.39, -0.13]). Tai Chi can also improve the balance ability of older adults, such as the timed up and go test (MD [95% CI]: -0.69 [-1.09, -0.29]) and the functional reach test (MD [95% CI]: 2.69 [1.14, 4.24]), as well as other balance tests such as single-leg balance test, Berg balance scale, and gait speed (p <0.05). Subgroup analysis showed that Tai Chi is effective for both healthy older adults and those at high risk of falls (p <0.001), and its effectiveness increases with the duration and frequency of exercise. In addition, the effect of Yang-style Tai Chi is better than that of Sunstyle Tai Chi.Tai Chi is an effective exercise for preventing falls and improving balance 4 ability in older adults, whether they are healthy or at high risk of falling. The effectiveness of Tai Chi increases with exercise time and frequency. Yang-style Tai Chi is more effective than Sun-style Tai Chi.